2002
DOI: 10.1163/15685390260514744
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Care in the Neotropical Harvestman Bourguyia Albiornata (Arachnida: Opiliones): Oviposition Site Selection and Egg Protection

Abstract: SummaryFemales of the harvestman Bourguyia albiornata oviposit almost exclusively inside the tube formed by the curled leaves of the bromeliad Aechmea nudicaulis. Oviposition is not correlated with rainfall or with temperature, but is negatively correlated with the number of individuals of A. nudicaulis emitting owers. Because the in orescence stalk occupies the tube of leaves of owering bromeliads, oviposition site is not available for ovigerous females. During one year, 83.6% of the females produced only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 33 publications
3
27
1
3
Order By: Relevance
“…Machado and Oliveira (2002) showed that B. hamata females oviposit almost exclusively inside the epiphytic bromeliad Aechmea nudicaulis at Cardoso Island, southeastern Brazil-even though this species represents only approximately 10% of the epiphytic bromeliads in the study area. Aechmea nudicaulis is a bromeliad with long curled leaves forming a tubular rosette that accumulates water (Wanderley and Mollo 1992;see also Fig.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Machado and Oliveira (2002) showed that B. hamata females oviposit almost exclusively inside the epiphytic bromeliad Aechmea nudicaulis at Cardoso Island, southeastern Brazil-even though this species represents only approximately 10% of the epiphytic bromeliads in the study area. Aechmea nudicaulis is a bromeliad with long curled leaves forming a tubular rosette that accumulates water (Wanderley and Mollo 1992;see also Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Each female found inside the individuals of A. nudicaulis was captured and classified according to her reproductive condition as non-reproductive, ovigerous (recognized through the enlarged abdomen with distended intersegmental membranes), or guarding (when taking care of eggs or nymphs). Each female received an individual mark with enamel paint and was released at the same bromeliad where she was found (following Machado and Oliveira 2002).…”
Section: Oviposition Site Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, individuals of some gonyleptid species seek diurnal refuge in caves and only leave at night to forage [49,50]. Several species inhabit leaf cutter ant nests [51], while others occupy bromeliads [52] or rely on bromeliads for reproduction [53]. Individuals of some temperate sclerosomatid species are known to make vertical migrations-climbing on trees during the day and descending at dusk to forage on or near the ground [6,17,18].…”
Section: Habitat Usementioning
confidence: 99%